INOVASI JEMPUT BOLA ADMINISTRASI KEPENDUDUKAN (JEBOL ANDUK) DALAM MENINGKATKAN KUALITAS PELAYANAN PUBLIK - Marselus Yollan Lokabora; Noora Fithriana (JISIP : Jurnal Ilmu Sosial dan Ilmu Politik, 2019)
Abstract: This study used a descriptive qualitative research method with the data sources were primary and secondary data. The data collection was gained through observation, interviews and documentation. The research instrument included the researcher himself, interview guidelines, and field notes. The technique of determining informants used a snowball sampling. While the data validity used triangulation technique and the data analysis techniques included data collection, data presentation and withdrawing conclusions / verification. The results of this study concluded that the service "Jebol Anduk", the proactive service, from the Department of Population and Civil Registration in Malang Regency has run well in supporting and improving the quality of public services. It can be seen from the service side that is in "Jebol Anduk" which was measured by using the theory of 6 (six) public service standards namely service procedures, completion time, service fees, service products, facilities and infrastructure, as well as the competence of service providers. But there are still some inhibiting factors such as the internet network that has not been maximized, the low of public awareness on the importance of population document ownership, as well as the lack of form availability from the central government for making E-KTP. Keywords: public service, service quality, innovation, "Jebol Anduk" Abstrak : Penelitian ini menggunakan metode penelitian deskriptif kualitatif, sumber data yang digunakan data primer dan data sekunder. Pengumpulan data dilakukan melalui observasi, wawancara dan dokumentasi. Instrumen penelitian meliputi peneliti sendiri, pedoman wawancara, dan catatan lapangan. Teknik penentuan informan menggunakan snowball sampling. Keabsahan data yang digunakan yaitu triangulasi teknik. Teknik analisis data meliputi pengumpulan data, penyajian data dan penarikan kesimpulan/verifikasi. Hasil dari penelitian ini menyimpulkan bahwa pelayanan “jebol anduk” Dinas kependudukan dan Pencatatan Sipil Kabupaten Malang sudah berjalan dengan baik dalam menunjang dan untuk meningkatkan kualitas pelayanan publik. Hal tersebut dapat dilihat dari sisi pelayanan yang ada ada pada “jebol anduk” yang diukur dengan menggunakan teori 6 (enam) standar pelayanan publik yaitu prosedur pelayanan, waktu penyelesaian, biaya pelayanan, produk pelayanan, sarana dan prasarana, serta kompetensi petugas pemberi pelayanan, tetapi masih terdapat beberapa faktor penghambat seperti jaringan internet yang belum maksimal, tingkat kesadaran masyarakat akan kepentingan kepemilikan dokumen kependudukan masih rendah, serta kurangnya ketersediaan blangko dari pemerintah pusat untuk pembuatan perekaman E-KTP. Kata Kunci : pelayanan publik, kualitas pelayanan, inovasi, “jebol anduk”